Organic Monolayers on Si(211) for Triboelectricity Generation: Etching Optimization and Relationship between the Electrochemistry and Current Output - Hurtado, Carlos; Lyu, Xin; Ferrie, Stuart; Le Brun, A.P.; Macgregor, M.; Ciampi, Simone (AMER CHEMICAL SOC, 2022)
Triboelectric nanogenerators (TENGs) based on sliding silicon-organic monolayer-metal Schottky diodes are an emerging autonomous direct-current (DC) current supply technology. Herein, using conductive atomic force microscopy and electrochemical techniques, we explore the optimal etching conditions toward the preparation of DC TENGs on Si(211), a readily available, highly conductive, and underexplored silicon crystallographic cut. We report optimized conditions for the chemical etching of Si(211) surfaces with subnanometer root-mean-square roughness, explore Si(211) chemical passivation, and unveil a relationship between the electrochemical charge-transfer behavior at the silicon-liquid interface and the zero-applied bias current output from the corresponding dynamic silicon-organic monolayer-platinum system. The overall aim is to optimize the etching and functionalization of the relatively underexplored Si(211) facet, toward its application in out-of-equilibrium Schottky diodes as autonomous power supplies. We also propose the electrochemical behavior of surface-confined redox couples as a diagnostic tool to anticipate whether or not a given surface will perform satisfactorily when used in a TENG design.